Batak Karo Alphabet Pattern Recognition - Oskar Ika Adi Nugroho (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2012)
Karo Batak script is typical and ancestral heritage of Batak tribe to preserve its existence. Currently Batak Karo script already has a standard of Unicode. Therefore, the authors develop models and handwriting recognition software Batak Karo script in real time. Real time or online is the way the introduction of OCR (Optical CharacterRecognize). Batak script used is Batak Karo alphabet has 20 types of characters. Model and software that is built using feature extraction zoning and consider the long strokes. The algorithm used is the Kohonen algorithm neuralnetwork. Kohonen neural network, including unsupervised learning (learning uncontrolled) by studying the distribution of the set of patterns without any class information.